First principles calculations of mechanical, electronic, thermoelectric and thermal properties of ZnCu - Yadav, Shashit Kumar; Dahal, Subash; Guragain, Bhupal (BIBECHANA, 2025)
The structural, elastic, electronic, thermoelectric, and thermal properties of ZnCu were investigated using Density Functional Theory (DFT). The Perdew–Burke–Ernzerhof (PBE) exchange-correlation functional within the Generalized Gradient Approximation (GGA) was employed in the Quantum ESPRESSO package for the purpose. The ZnCu compound was found to be both mechanically and dynamically stable. Analysis of its elastic and electronic properties reveals that ZnCu is mechanically stable, anisotropic, and exhibits metallic behavior. Furthermore, thermoelectric property analysis indicates that ZnCu achieves its highest power factor at 300 K. The study of thermodynamic properties suggests that ZnCu retains mechanical stability at elevated temperatures. Additionally, the specific heat capacity shows a significant increase at low temperatures and approaches a constant value at high temperatures, consistent with phonon excitation behavior.